Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12942-017-0112-x
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural inequalities in suicide mortality: a comparison of urbanicity indicators

Abstract: BackgroundUrban–rural disparities in suicide mortality have received considerable attention. Varying conceptualizations of urbanity may contribute to the conflicting findings. This ecological study on Germany assessed how and to what extent urban–rural suicide associations are affected by 14 different urban–rural indicators.MethodsIndicators were based on continuous or k-means classified population data, land-use data, planning typologies, or represented population-based accessibility indicators. Agreements be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 60 publications
3
35
1
6
Order By: Relevance
“…Similar finding also found from a study in Iran. (Mohammadi et al, 2005), however a study in Germany showed different findings (Helbich et al, 2017). Education has been known as the crucial aspect in enable individual to cope stressors, however lower education not necessaryly reffers to lower stress coping, as it may confound with other social, cultural, economy and psychological determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding also found from a study in Iran. (Mohammadi et al, 2005), however a study in Germany showed different findings (Helbich et al, 2017). Education has been known as the crucial aspect in enable individual to cope stressors, however lower education not necessaryly reffers to lower stress coping, as it may confound with other social, cultural, economy and psychological determinants.…”
Section: Discussionmentioning
confidence: 99%
“…However, research ( Blüml et al, 2017 , Helbich et al, 2015 ) remains on a coarse analytical scale focusing on intra-regional differences, which is too crude to explore how area-level urban environmental exposures correlate with mental health. As residential neighborhoods matter for health outcomes ( Diez Roux and Mair, 2010 , Macintyre and Ellaway, 2000 , Sampson et al, 2002 ), it is reasonable to analyze mental health within cities on a detailed scale beyond the crude urban–rural dichotomy ( Peen et al, 2010 , Helbich et al, 2017 , Liu et al, 2015 ). Inter-urban study designs markedly increase the conceptual and methodological complexity of analyses, as environmental exposures not only directly affect people's mental health, but also moderate other risk and protective factors.…”
Section: From Static To Dynamic Exposure Assessmentsmentioning
confidence: 99%
“…England and Wales (Gunnell et al, 2012;Middleton et al, 2004), Germany (Helbich et al, 2017a) and the United States (Trgovac et al, 2015). More than half of the world's population now resides in urban areas (United Nations, 2014).…”
Section: Introductionmentioning
confidence: 99%